EVALUATION OF ENZYME REPLACEMENT THERAPY EFFECTIVENESS IN CHILDREN WITH GAUCHER'S DISEASE ACCORDING TO THE INTERNATIONAL STUDIES - O. S. Gundobina; G. B. Movsisyan; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2014)
The article presents data on the history of creation of pathogenetic enzyme replacement therapy and its introduction into clinical practice of managing patients with Gaucher's disease. 2 primary stages are distinguished: beginning of use of enzyme β-D-glycosidase analog obtained from placenta and alglucerase; introduction of recombinant glucocerebrosidase (imiglucerase). The article demonstrates that enzyme replacement therapy is the only efficient method of treating Gaucher's disease; according to the international studies; it terminates the primary clinical manifestations of the disease, thus improving quality of life of the patients without any marked side effects. Imiglucerase is used at present; it causes hydrolysis of glycolipid glucocerebroside down to glucose and ceramide by the common way of metabolism of membrane lipids. Imiglucerase is indicated for long-term enzyme replacement therapy in patients with confirmed Gaucher's disease (types 1 and 3).